FROM DISRUPTION TO MOBILIZATION: IRE TEACHERS’ PERSPECTIVES ON INDEPENDENT LEARNING POLICY - Muhammad Thohir; Samsul Maarif; Junaedi Rosyid; Hisbullah Huda; Ahmadi Ahmadi (LPMPP Universitas Negeri Yogyakarta, 2021)
The policy on Independent Learning was established by the Indonesian government to promote teacher performance in midst of disruption in the educational aspect during this COVID-19 pandemic. However, teachers may not share the same perspective related to the policy. This study aims to examine Islamic Religious Education (IRE) teachers’ perspectives on Independent Learning policy. The research participants were IRE teachers who passed the 2019 In-service Teacher Profession Training Program at a State Islamic University in East Java, Indonesia. The mix-method research design with a qualitative-quantitative sequential exploratory analysis was used in this study. Qualitative data were obtained through telephone interviews, non-participant observations, and investigative documentary tracing, while quantitative data were obtained through a survey using online questionnaires. The collected data were analyzed using the descriptive qualitative phenomenological technique and descriptive statistics. The findings show that the increase in the use of mobile learning by IRE teachers is an implication of the disruption leading to the mobilization of the educational sector to approach the Independent Learning policy based on performances in three perspectives. First, the policy is considered a critique of traditional educational practices. Second, the policy serves as a space for independence with rules and regulations that are more open for students and schools. Third, the policy is an effort to free education from social and political pressures and restraints. This study provides a new understanding of the philosophical inter-connection in teachers’ perceptions to the practice of distant learning implementation based on informational technology.